2020
DOI: 10.3390/biology9070172
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Static Magnetic Field on Growth, Pigments, Osmolytes, Nitric Oxide, Hydrogen Sulfide, Phenylalanine Ammonia-Lyase Activity, Antioxidant Defense System, and Yield in Lettuce

Abstract: Magnetic fields are an unavoidable physical factor affecting living organisms. Lettuce seeds (Lactuca sativa var. cabitat L.) were subjected to various intensities of the static magnetic field (SMF) viz., MF0 (control), SMF1 (0.44 Tesla (T), SMF2 (0.77 T), and SMF3 (1 T) for three exposure times (1, 2, and 3 h). SMF-treated seedlings showed induction in growth parameters and metabolism comparing to control. All photosynthetic pigments were induced markedly under SMF, especially chlorophyll a. SMF at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 78 publications
(86 reference statements)
2
11
0
Order By: Relevance
“…Our results showed that under salinity treatment, Faradarmani CF ameliorated the adverse effects of salt stress, probably by improving antioxidant systems, scavenging ROS and increasing the chlorophyll a and b contents (Figure 1). Similar findings were presented by screening the effect of the Static Magnetic Field (SMF) on pigments in Lettus and it has been reported that all photosynthetic pigments, especially chlorophyll a increased under the influence of SMF and this positive result was associated with improvement of antioxidant system (Latef et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that under salinity treatment, Faradarmani CF ameliorated the adverse effects of salt stress, probably by improving antioxidant systems, scavenging ROS and increasing the chlorophyll a and b contents (Figure 1). Similar findings were presented by screening the effect of the Static Magnetic Field (SMF) on pigments in Lettus and it has been reported that all photosynthetic pigments, especially chlorophyll a increased under the influence of SMF and this positive result was associated with improvement of antioxidant system (Latef et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Magnetic treatment can be used to mitigate stress caused by the environment. The reduction in H2O2 and O2 levels in magnetized water treatment confirms that the magnetic field can control the production of ROS (Latef et al 2020).…”
Section: Discussionmentioning
confidence: 65%
“…The magnetic field has a potential effect on the antioxidant system of the cells, and MF is involved in antioxidant-modulated response in the apoplast, causing tight control of the redox status disturbance (Cakmak et al 2012). The beneficial effect of a magnetic field on lettuce plant growth may be due to maintaining an equilibrium between ROS production and scavenging (Latef et al 2020). Compared to controls, magnetized water treatment can reduce levels of anthocyanin, H2O2, malondialdehyde (MDA), and superoxide dismutase (SOD).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh samples were homogenized in the extraction solution, centrifuged at 18 000 × g at 4 °C for 15 min, and stored in darkness for 5 h at 5 °C. The amount of anthocyanin was quantified at 550 nm spectrophotometrically (Abdel Latef et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%